Muscle and sensory testing - Nancy Berryman Reese; ClinicalKey (St. Louis Missouri : Elsevier, 2021)
Mastering the art of manual muscle and sensory testing is the first step on your path to becoming a physical therapist (PT). This easy-to follow, logically organized resource includes an overview of muscle strength assessment and precise anatomic testing techniques for upper extremities, lower extremities, and head, neck, and trunk; functional muscle tests; tests for mental status, cranial nerves, and superficial reflexes; and use of observational gait analysis as a screening tool
Keywords: Afferent pathways Testing; Applied kinesiology